Draft problems - Davis, Guy R. (My University, 1905)
Introduction: Every modern agriculturist of today should have a fairly accurate knowledge of the draft required for pulling the different implements on the farm under varying conditions. That this question should be seriously considered by all farmers can easily be proven by a large number of experiments which show that some machines require more draft power than others for the accomplishment of the same kind and the same amount of work. Before giving any data obtained by the writer or by others, it may be well to give a description of the instrument, which is called the dynamometer, by means of which the draft is determined, and also give some general facts about the subject. The dynamometer is an instrument for measuring the force or weight required to pull a load on a wagon or draw a machine as it works in the field. The dynamometer is made a link in the draught chain and thus subjected to the tension which it is desired to ascertain. The kind of instrument which is used mostly today, especially where the draft is variable as with all agricultural implements, is a self -recording dynamometer. According to the Michigan Agricultural Experiment Station report the earliest notice that we have that horses were used in field labor is from the figure on a piece of tapestry woven at Bayonne in the time of William the Conqueror, 1066 A.D. On this tapestry was a figure of a man driving a horse attached to a harrow. Up to within the last century or two it has been the practice in Briton to hitch horses to the plow or harrow by means of withes tied to the tails of the animals. McDonald in his Survey of the Hebrides in 1808, says, "the common practice was to fasten horses and colts by the tail to the harrow," although in 1634 a law was passed against this custom. Another law of the early Britons was "that no L one should guide a plow until he could make one and that the driver should make the traces by which the plow was drawn of withes or twisted willows."
The study of draft problems
Citation: Davis, Guy R. Draft problems. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Powing; Draught Power; Sliding Coulter; Theses